In vitro germination and micropropagation of Myracrodruon urundeuva Allemão (Anacardiaceae) - Vinicius de Souza Nascimento, Augusto; Mendonça, Ane Marcela das Chagas; da Silva Júnior, Carlos Dias; de Santana, Marlucia Cruz; Santos, Paulo Augusto Almeida (Plant Cell Culture & Micropropagation - ISSN 1808-9909, 2020)
Myracrodruon urundeuva is a native tree species that stands out for the use of its wood and for medicinal purposes. Due to the multiple uses and extractive exploitation, this species has been threatened with extinction. Thus, it is important to develop strategies in order to ensure conservation and long term exploitation. This work aimed to establish a protocol of in vitro seed germination and micropropagation of M. urundeuva. Different support agents (vermiculite and agar) and presence of sucrose were tested for in vitro germination, while different concentrations of BAP (0.0, 0.5, 1.0 and 2.0 mg L-1) and explant types (apical and cotyledonary) were tested for multiplication. The use of vermiculite as a support agent favored in vitro germination of M. urundeuva, with germination percentage of 64.3% and 32% for vermiculite and agar, respectively. No significant differences were observed for the different BAP concentrations tested in multiplication and the treatment with 1.0 mg L-1 BAP presented higher values for most variables analyzed. Cotyledonary explants presented higher number of shoots (1.6 shoots) compared to the apical ones (1.1 shoots). Vermiculite may be used as a replacement for agar for in vitro seed germination and the combination of 1.0 mg L-1 of BAP and cotyledonary explants may be used for in vitro multiplication of M. urundeuva. Furthermore, studies are needed to improve in vitro multiplication methods of this species.